Financial Situation of Soviet Citizens in the Mirror of Public Opinion of 1960-1980s (according to Letters to the Central Authorities and the Media) - A. S. Stoletova (Научный диалог, 2020)
Based on the archival sources first introduced into the scientific community, the article highlights the question of the material well-being of Soviet citizens in estimates of the mass consciousness of the 1960s and 1980s. Within the framework of the problems, the well-being of citizens, which are the drivers of the socio-economic development of the state, are considered. In addition, the mental side of the processes is affected. The question is raised of social stratification, the beginning of the formation of a new structure of society as the realities of the second half of the 20th century. It is noted that in the public environment, vigilant monitoring of the excessive enrichment of persons in leadership positions was conducted. Based on the analysis of the material database of the Russian State Archive of Recent History, the author concludes that the trend of the time was the increase in the number of illegal acquisitions in three areas: housing, motor transport, personal household plots. A problem related to modernization processes in the spiritual sphere of life in Soviet society is raised. It is shown that there were changes in the behavioral stereotypes of social classes in the development of the right to use socialist property in this area, in relation to things and the desire for a comfortable life in society. It is concluded that the global consequence of these phenomena is the affirmation of private property morality.